Soil enzyme activities, soil physical properties, photosynthetic physical characteristics and water use of winter wheat after long-term straw mulch and organic fertilizer application - Yang, Yonghui; Liu, Hao; Wu, Jicheng; Zhang, Sensen; Gao, Cuimin; Zhang, Shuiqing; Tang, Darrell W. S. (Frontiers in Plant Science, 2023)
Inappropriate tillage measures lead to soil degradation and the decline of soil quality and water storage capacity. An ongoing field experiment has been conducted since 2011 to investigate the effects of straw mulching (SM), and straw mulching combined with organic fertilizer (SM+O), on winter wheat yield, including a control treatment (CK, no straw). We studied the effects of these treatments on soil microbial biomass nitrogen and carbon, soil enzyme activity, photosynthetic parameters, water consumption, water use efficiency (WUE), and yields over five consecutive years (2015 – 2019). We also analyzed the soil organic carbon, soil structure, field capacity, and saturated hydraulic conductivity in 2015 and 2019. Results indicate that compared with CK, SM and SM+O treatments increased the proportion of >0.25mm aggregates, soil organic carbon, field capacity, and saturated hydraulic conductivity, but decreased the soil bulk density. In addition, the SM and SM+O treatments also increased soil microbial biomass nitrogen and carbon, the activity of soil enzymes, and decreased the carbon-nitrogen ratio of microbial biomass. Therefore, SM and SM+O treatments both increased the leaf water use efficiency (LWUE) and photosynthetic rate (Pn), and improved the yields and water use efficiency (WUE) of winter wheat. The combination SM+O was more effective than SM alone, and both treatments were superior to the control.